2017
DOI: 10.1016/j.jasrep.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

On sourcing obsidian assemblages from the Mediterranean area: analytical strategies for their exhaustive geochemical characterisation

Abstract: This paper presents an overview of the work conducted by our research group in the Mediterranean area. Initiated in the 1990s by the late Gérard Poupeau, our research relies on international and multidisciplinary collaborations to endeavour archaeological and anthropological issues linked to the diffusion and consumption of the obsidian raw material during the Neolithic period. Our line of action is to develop flexibly unique analytical strategies, tailored to each obsidian assemblage considered for a sourcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…At the same time, this paper makes no claim to offer an “ideal” methodological protocol in any sense of the term (see Orange et al . ). New Zealand has a comparatively complex geology and, importantly for provenancing studies, some geographically distant sources have similar compositions, necessitating the use of fine‐grained discrimination methods.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, this paper makes no claim to offer an “ideal” methodological protocol in any sense of the term (see Orange et al . ). New Zealand has a comparatively complex geology and, importantly for provenancing studies, some geographically distant sources have similar compositions, necessitating the use of fine‐grained discrimination methods.…”
Section: Discussionmentioning
confidence: 97%
“…To make the fullest use of these data, it is essential to review established sourcing methods from time to time and, if they are found to be inadequate, explore new approaches (Orange et al . ; Stroth et al . ; see also Glascock et al .…”
Section: Pxrf Technology and Obsidian Characterisation Studiesmentioning
confidence: 99%
“…The analyses were carried out at the Research Centre for Applied Physics in Archaeology, IRAMAT, Bordeaux, France. Nine elements were quantified (Na, Mg, Al, Si, P, K, Ca, Ti, Fe) using an X‐ray fluorescence spectrometer SEIKO SEA 6000VX (Orange et al , ). Fundamental parameters corrected by the granodiorite GSP2 from the US Geological Survey (USGS) international standard (Wilson, ) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Energy dispersive X-ray fluorescence (ED-XRF) has since been established, and hand-held models of XRF have become a preferred instrument for being portable, non-destructive, and increasingly, trace element detection abilities. pXRF and lab XRF have been compared (Craig et al, 2007), and recently pXRF analyses have been integrated with analyses using other instruments and methodologies (Orange et al, 2017). The literature on pXRF and obsidian is vast, and suffices here to say that the instrument has sufficient detection abilities to discriminate among sources and subsources within a continental area, with some current instruments achieving high levels of precision (Tykot, 2016).…”
Section: Stratigraphicmentioning
confidence: 99%